Agricultural E-Commerce: A New Business Platform for Smallholders in Quirino Province - Duldulao, Jay-R Roy; Concepcion, Joselle Dela Cruz; Duldulao, Arsenia Valdez (International Journal of Computing Sciences Research, 2023)
Purpose – ICTs play a vital role in achieving sustainable agricultural development when they are used to record both organic and conventional farming practices.  The move to more sustainable agriculture techniques depends on smallholders.  The province of Quirino has been recognized as one of the top food producers in the nation and worked hard to provide high-quality items that are shipped to neighboring provinces and areas.  This study aims to develop a multi-vendor e-commerce platform where vendors can add their own products. Method – This study utilized a descriptive and developmental research method. A set of questionnaires were given to the respondents based on the ISO 25010 software quality standards.  Problems were reframed using the design thinking process and concepts were developed for prototyping and testing.  The system was developed by utilizing the Scrum framework. Results – The developed platform allows vendors to set up their own stores and add their own products. Transport services are also available but limited to flatrate shipping and local pickup. It also supports modes of payment, but they are limited to cash on delivery, DragonPay, Globe Gcash, and UnionPay.  The IT experts assessed the extent of compliance of the developed system to ISO 25010 to a very great extent and therefore, ready for deployment and implementation.   Conclusion – The developed system can utilize product-search matching to connect the farmers with their intended customers and vice versa. The vendors can add more products in their module, set the price and can schedule discounts.  Product inventories are also displayed in the vendors module. Recommendations – The inclusion of data analytics, a mobile app for iOS and Android, as well as various business models can all be taken into consideration to further improve the system. Practical Implications – Using the multi-vendor e-commerce platform, this research will benefit the buyers and sellers by allowing them to buy and sell their products.